Validating the 6 year (2016–2021) anthropogenic induced small island wildfire hazards in Pulau Seribu archipelago, Indonesia - Lestari, Fatma; Adiwibowo, Andrio; Kadir, Abdul; Ramadhan, Noor Aulia (Progress in disaster science, 2022)
Due to their specific characteristics, small islands tend to face unique challenges, including the challenges posed by wildfire threats caused by the presence of volatile vegetations and anthropogenic influences. This study aims to validate the impacts of the anthropogenic influence on wildfire risks for the period of 2011–2021 in several occupied small islands in Pulau Seribu archipelago, including Tidung and Pari Islands. An uninhabited island, Tidung Kecil Island, was used as control. To validate the anthropogenic influences on wildfire presences, the ANOVA one-way and Receiver Operating Characteristic (ROC) methods were used. Results show that human occupancy has significantly contributed to the wildfire frequency and burnt area size (F = 4.413, p = 0.001), with the occupied islands have the highest wildfire frequencies of 0.45 cases annually, and the highest burn area average of 4076 m2 annually. The uninhabited island only experiences 0.09 wildfires per year. Wildfires occur both day and night. Daytime wildfires were mostly caused by improper disposal of cigarette butts or smoking activities. In contrast, nighttime wildfires were caused by open waste burning and camping activities.The validation using the ROC, with an area under the ROC curve value (AUC) of 0.671 (95%CI: 0.301–1), has validated the accuracy that the anthropogenic factors are proxies for wildfire hazards in Tidung Island. However, the accuracy of the anthropogenic influence-wildfire hazard association in Pari Island is slightly lower with an AUC of 0.633 (95%CI: 0.321–0.946). These confirm the potential of anthropogenic influences as a proxy for wildfire, especially in Tidung Island. •Wildfires are significant common hazards in small islands.•Wildfires are due to the flammable vegetation and anthropogenic activities.•In Indonesia, occupied small islands were experiencing more wildfires.•Grass species dominances in small island are also contributing to the wildfires.